Combined partial deficiency of muscle carnitine palmitoyltransferase and carnitine with autosomal dominant inheritance. Issue 8 (August 1980) - Ionasescu, V; Hug, G; Hoppel, C
Abstract : The authors studied a 53 year old woman and her 22 year old son with episodes of paroxysmal muscle cramps and dark urines lasting several hours related to high fat diet and strenuous physical exercise beginning on both at age 14 years. The father, paternal uncle, paternal grandfather and another son of the mother also had paroxysmal muscle cramps. The two studied cases showed normal findings for physical evaluation, blood lactate after ischemic exercise, and muscle histology (light and electron microscopy). The serum creatine kinase was elevated in the son and normal in the mother. However, 72 hour fasting significantly raised the serum creatine kinase level in both cases. Plasma concentration of ketone bodies and acid soluble acyl-carnitine increased normally with prolonged fasting. The biochemical evaluation of the muscle tissue revealed intact anaerobic glycolysis and normal glycogen content but combined partial deficiency of muscle carnitine palmitoyltransferase and carnitine in both cases.